Normal Performance in Non-Visual Social Cognition Tasks in Women with Turner Syndrome - Anaki, David; Zadikov-Mor, Tal; Gepstein, Vardit; Hochberg, Ze’ev (Frontiers in Endocrinology, 2018)
Turner syndrome (TS) is a chromosomal disorder in women resulting from a partial or complete absence of the X chromosome. In addition to physical and hormonal dysfunctions, along with a unique neurocognitive profile, women with TS are reported to suffer from social functioning difficulties. Yet, it is unclear whether these difficulties stem from impairments in social cognition per se or from other deficits that characterize TS but are not specific to social cognition. Previous research that has probed social functioning in TS is equivocal regarding the source of these psychosocial problems since they have mainly used tasks that were dependent on visual-spatial skills, which are known to be compromised in TS. In the present study, we tested 26 women with TS and 26 matched participants on three social cognition tasks that did not require any visual-spatial capacities but rather relied on auditory-verbal skills. The results revealed that in all three tasks the TS participants did not differ from their control counterparts. The same TS cohort was found, in an earlier study, to be impaired, relative to controls, in other social cognition tasks that were dependent on visual-spatial skills. Taken together these findings suggest that the social problems, documented in TS, may be related to non-specific spatial-visual factors that affect their social cognition skills.